M&A Value Creation and Derivatives Usage of Acquiring Firms : Finnish evidence Q1/2010-Q2/2025 - Weck, Henri (My University, 2026)
Mergers and acquisitions (M&A) are among the most significant investment decisions made by corporate management and are generally expected to create value through synergies, growth and more efficient use of capital. Success in these deals does not only depend on operational integration but more importantly on whether they lead to a positive development in return on invested capital relative to the required return on capital. In addition, M&A deals may increase financial risks, and when managing them derivatives hold an important role. Based on the described premise, this thesis examines the relationship between M&A activity, value creation and derivatives usage in Finnish listed firms during 2010–2025. The empirical reseach focuses on firms listed in Nasdaq Helsinki, excluding companies in the investment and financial sectors, that completed at least one M&A deal during the observation period. Financial value creation is measured by using economic spread, also know as ROIC-WACC spread, by comparing changes in it before and after M&A deals. The spread describes the difference between return on invested capital and the cost of capital. The research data has been compiled by combining firm-specific M&A and financial statement data on a quarterly basis. Derivatives usage is defined based on financial statement disclosures and the research examines it as an independent firm-specific control and as well as together with M&A activity. The research models also include firm-specific control variables such as size, growth, leverage, profitability and asset tangibility. The empirical analysis is based on OLS regressions that use four different specifications of deal activity, including a comparison between individual deal quarters and no-deal quarters, a linear measure of the number of deals completed in a quarter, an indicator for quarters with multiple deals and a logarithmic transformation of deal intensity. Based on the results, M&A activity is mostly associated with positive changes in the ROIC–WACC spread. This suggests that M&A deals can support financial value creation, particularly over shorter observation windows. However, the statistical evidence is not entirely consistent across different models and time periods. Derivatives usage has a relatively weakening effect on the benefits derived from M&A deals and the results therefore provide no clear evidence that derivative usage supports the value creation. The results highlight the usefulness of M&A deal making in value creation, while also indicating that related risk management through derivatives should be assessed individually in each case.

Yrityskauppatransaktiot kuuluvat yritysjohdon merkittävimpiin investointipäätöksiin ja niiden odotetaan lähtökohtaisesti luovan arvoa synergioiden, kasvun sekä pääoman tehokkaamman käytön kautta. Tässä onnistuminen ei kuitenkaan riipu ainoastaan operatiivisesta integraatiosta vaan ennen kaikkea siitä, johtavatko ne sijoitetun pääoman tuoton myönteiseen kehitykseen suhteessa pääoman tuottovaatimukseen. Tämä on olennaista, koska strategisesti perusteltu transaktio ei välttämättä luo arvoa, mikäli sen tuotto ei ylitä pääoman kustannusta. Yrityskaupat voivat myös kasvattaa korko-, valuutta-, velka- ja kassavirtariskejä, joiden hallinnassa hyödynnetään usein johdannaisia. Näistä lähtökohdista tämä tutkielma tarkastelee yrityskauppa-aktiivisuuden, arvonluonnin ja johdannaisten käytön välistä yhteyttä suomalaisissa pörssiyhtiöissä vuosina 2010–2025. Empiirinen tutkimus keskittyy Nasdaq Helsingissä listattuihin yhtiöihin, poislukien sijoitus- ja rahoitusalan yhtiöt. Tutkimus koostuu yhtiöistä, jotka ovat toteuttaneet vähintään yhden yrityskauppatransaktion tarkastelujakson aikana. Taloudellista arvonluontia mitataan ROIC WACC-eron muutoksella yrityskaupan jälkeen suhteessa sitä edeltävään aikaan ja se kuvaa sijoitetun pääoman tuoton ja pääoman kustannuksen välistä erotusta. Tutkimusaineisto koostuu yrityskohtaisista yrityskauppa- ja tilinpäätöstiedoista kvrartaalitasolla. Johdannaisten käyttö määritellään tilinpäätöstietojen perusteella ja sitä tarkastellaan sekä itsenäisenä kontrollimuuttujana että yhdessä yrityskauppa-aktiivisuuden kanssa. Tutkimusmalleihin kuuluu myös kontrollimuuttujia, kuten koko, kasvu, velkaisuus, kannattavuus ja aineellisten hyödykkeiden osuus. Empiirinen analyysi perustuu OLS-regressioihin, joissa yrityskauppa aktiivisuutta mitataan neljällä vaihtoehtoisella tavalla: yrityskauppakvartaalien ja yrityskaupattomien kvartaalien vertailulla, yrityskauppojen lineaarisella mittauksella, useita yrityskauppoja sisältävien kvartaalien mittauksella sekä yrityskauppojen intensiteetin logaritmisella mittauksella. Tulosten perusteella yrityskauppa-aktiivisuus on enimmäkseen yhteydessä ROIC–WACC-eron myönteiseen muutokseen. Tämä viittaa siihen, että yrityskaupat voivat tukea taloudellista arvonluontia erityisesti lyhyemmillä tarkastelujaksoilla. Tilastollinen näyttö ei kuitenkaan ole täysin johdonmukaista eri mallien ja ajanjaksojen välillä. Tulosten perusteella johdannaisten käytöllä on suhteellisesti yrityskaupoista saatavia hyötyjä heikentävä vaikutus eivätkä tulokset tarjoa selvää näyttöä siitä, että johdannaisten käyttö tukisi arvonluontia yrityskaupoissa. Tulokset korostavat yrityskauppojen hyödyllisyyttä arvonluonnissa, mutta osoittavat, että niihin liittyvää johdannaisilla toteutettavaa riskienhallintaa tulisi arvioida tapauskohtaisesti.
Keywords: corporate acquisitions; value creation; derivative securities; risk management; capital costs; capital investment; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance